The Burden of Empirical Therapy: Analyzing the Predominance of Broad-Spectrum Antibiotic Usage in Lower Respiratory Tract Infections - Jeuti Talukdar (International Journal of Antibiotics, 2026)
Lower respiratory tract infections (LRTIs) remain one of the leading causes of morbidity and hospitalization worldwide, particularly among older adults, immunocompromised individuals, and patients with chronic respiratory disorders. These infections include conditions such as community-acquired pneumonia, hospital-acquired pneumonia, bronchitis, and acute infective exacerbations of chronic lung disease, all of which often require rapid clinical intervention. Because microbiological confirmation of the causative pathogen frequently takes 48–72 hours, clinicians generally initiate empirical antibiotic therapy at the time of admission to prevent disease progression and reduce mortality. In many tertiary care hospitals, this empirical treatment commonly relies on broad- spectrum antibiotics to ensure coverage against a wide range of suspected bacterial pathogens, including resistant organisms. Although this approach is clinically justified during the initial management phase, prolonged or inappropriate use of broad-spectrum agents contributes significantly to antimicrobial resistance, increased treatment costs, adverse drug reactions, and disruption of normal microbial flora. This study evaluates the burden of empirical antibiotic therapy in lower respiratory tract infections within a tertiary care setting, with particular emphasis on prescribing trends, the predominance of broad-spectrum antimicrobial agents, and the importance of antibiotic de-escalation after microbiological or clinical reassessment. De-escalation strategies are essential for optimizing therapy, improving patient outcomes, and supporting antimicrobial stewardship practices. A prospective observational study was carried out over a six-month period in a tertiary care teaching hospital located in Jalandhar to evaluate antibiotic prescribing practices among patients diagnosed with respiratory tract infections. The study included 100 hospitalized patients who met predefined clinical and diagnostic criteria for lower respiratory tract infections, including pneumonia, acute bronchitis, and infective exacerbations of chronic respiratory diseases. Demographic details, clinical presentation, laboratory findings, microbiological reports, and antibiotic prescriptions were systematically recorded from patient case sheets and treatment charts throughout the hospital stay. Particular emphasis was placed on identifying the empirical antibiotics prescribed at admission and classifying them according to their antimicrobial spectrum as broad-spectrum or narrow-spectrum agents. The study also assessed the prevalence and distribution of lower respiratory tract infections among different age groups and clinical categories. Subsequent changes made to the initial antibiotic regimen were carefully documented, including escalation to broader agents when clinical response was inadequate and de-escalation to narrower-spectrum therapy once microbiological culture reports or clinical improvement supported targeted treatment. This observational approach provided valuable insight into real-world prescribing behavior, antibiotic utilization trends, and the practical implementation of antimicrobial stewardship principles in the management of respiratory infections in a tertiary care setting. The study identified a heavy burden of LRTIs, which constituted 87% of all cases , with pneumonia being the leading diagnosis (30%). Empirical therapy was heavily reliant on broad-spectrum antibiotics, which were prescribed in 89% of cases. This predominance was driven by a significant diagnostic gap, as 80% of cultures yielded no identifiable microorganism. Despite the high initial burden of broad-spectrum use, antibiotic de- escalation was successfully implemented in 46% of patients, primarily through dose reduction and spectrum narrowing. Conclusions: The predominance of broad-spectrum antibiotic usage reflects the necessity of empirical coverage for LRTIs in elderly and comorbid populations where pathogen identification is often absent. While this "burden of empirical therapy" is high, it is effectively managed through responsive de-escalation strategies, highlighting the critical role of antimicrobial stewardship in balancing empirical needs with resistance prevention.
Keywords: Antibiotic stewardship; Broad-Spectrum Antibiotics; De-escalation; Empirical Therapy; Lower Respiratory Tract Infections